Wireless Systems and Mobility in Next Generation Internet 4th International Workshop of the EuroNGI/EuroFGI Network of Excellence Barcelona, Spain, January 16-18, 2008. Revised Selected Papers - Cerdà-Alabern, Llorenç (Computer Communication Networks and Telecommunications, 2008)
This book constitutes the thoroughly refereed post-workshop proceedings of the 4th International Workshop on Wireless and Mobility organized inside the Euro-NGI/FGI Network of Excellence and held in Barcelona, Spain, in January 2008. The 16 revised full research papers presented were carefully selected from 39 submissions during two rounds of reviewing and improvement. The papers are organized in topical sections on sensor networks, mesh networks, mobile ad-hoc networks, and cellular networks.